THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) THROUGH ORGANIZATIONAL COMMITMENT AND TRUST IN LEADERS AS MEDIATION - Pratama, Lutfi Adi; Putri, Vini Wiratno (Universitas Negeri Semarang, 2019)
The purpose of this study to explain the influence of transformational leadership on organizational commitment OCB through commitment and trust in the leader. The population in this study were employees of the Office of the Regional Secretariat of Semarang City with a sample of 126 respondents. Sampling using proportional random sampling technique. Methods of data collection in this study using a questionnaire that measured using a scale linkert. Methods of data analysis used in this study using SmartPLS 3.0. Based on the results of the research, it was found that there was no influence of transformational leadership on OCB, there is influence between organizational commitment on OCB, there is no influence of trust on the leader of the OCB, organizational commitment mediates the relationship between transformational leadership on OCB, confidence in leaders did not mediate the relationship between transformational leadership on OCB. The conclusion by improving organizational commitment of employees, it can grow OCB employee. Suggestions for the organization to further improve the organizational commitment of every employee and pay more attention to the factors of transformational leadership.